Notes sur le « primitivisme » - Jehanne Denogent (Contextes)
This article focuses on the historiography of primitivism, understood as the interest shown in non-Western cultures by the avant-garde. Emerging with the development of anthropology, this movement arouses a debate between anthropological and aesthetic studies. I will distinguish three steps in this disciplinary negotiation around primitivism, after observing the issues at stake as they arose for the actors of the avant-garde. The first describes a formal approach, illustrated by the work of Robert Goldwater and Jean Laude, the second addresses the criticisms made by James Clifford and the last evokes two recent works on the question, by Ben Etherington and Philippe Dagen.